Minutes and financial records of the Social Democratic Workingmen's Party, Philadelphia, Pa. - Social Democratic Workingmen's Party (Philadelphia, Pa.)
Minutes and financial records.
Collection material in English, with German.
Keywords: Socialist parties -- Pennsylvania -- Philadelphia; Working class -- Pennsylvania -- Philadelphia; Philadelphia (Pa.) -- Politics and government